Gradient multifunctional biopolymer thin film assemblies synthesized by combinatorial MAPLE - TOKSOY ÖNER, EBRU; EROĞLU, MEHMET SAYIP; SENNAROĞLU BOSTAN, MÜGE (ELSEVIER SCIENCE BV, 2019)
Combinatorial Matrix-Assisted Pulsed Laser Evaporation (C-MAPLE) was recently introduced to the fast generation of compositional libraries of two biopolymers in a single-step process, for tissue engineering and regenerative medicine applications. Synchronized laser irradiation of two distinct cryogenic targets, one consisting of Sulfated Halomonas Levan and the other of quaternized low molecular weight Chitosan was used to fabricate compositional gradient coatings for surface functionalization. Synthesized coatings preserved the base material composition as confirmed by Fourier Transform Infrared Spectroscopy. Morphological study by Scanning Electron Microscopy, Atomic Force Microscopy and profilometry correlated with water contact angles measurements demonstrated that the obtained thin coatings have improved surface properties with respect to pure material coatings. Fluorescence microscopy validated the compositional gradient, while in vitro assays evidenced characteristic responses of mouse fibroblasts (L929 cell line) by distinct deposition surface regions. The coagulation test pointed out good properties for Sulfated Halomonas Levan coatings as compared to the case of an increased amount of quaternized low molecular weight Chitosan biopolymer or the control. The antimicrobial effect of the coatings was demonstrated against Escherichia coli and Staphylococcus aureus strains, representative for both Gram negative and Gram positive bacterial species, respectively, mainly involved in implant and nosocomial infections. The assembled nanostructures possess variable anti-biofilm activity along the compositional gradient, with a stronger inhibitory effect on the initial adherence phase of both tested microbial strains, but also against mature Escherichia coli biofilms. It was shown that C-MAPLE can generate discrete areas of blended polymeric composition exhibiting improved surface properties for a broad range of biomedicine applications, e.g. the fabrication of thin bioactive and cell-instructive coatings with anti-adherence properties.
Keywords: Combinatorial-MAPLE; Biopolymer coatings; Compositional maps; Sulfated Halomonas Levan - quatern zed low; molecular weight Chitosan mixtures; Anti-biofilm activity; MOLECULAR-WEIGHT; HALOMONAS-SMYRNENSIS; ANTICOAGULANT ACTIVITY; ANTIMICROBIAL ACTIVITY; SULFATED LEVAN; CELL-ADHESION; CHITOSAN; COATINGS; DERIVATIVES; DELIVERY